2017
DOI: 10.1515/pjvs-2017-0052
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Synthetic Sex Pheromones in Sexual Arousal Stimulation in Domestic Dogs

Abstract: The aim of this study was to evaluate the suitability of synthetic bitch sex pheromones (Eau' De Estrus ® , Synbiotics USA) for the stimulation of the reproductive reflexes in adult male dogs. In experiment I: anoestral bitches were applied synthetic (n=6) or natural (n=6) pheromones and their attractiveness was compared to the attractiveness of bitches in natural oestrus, In experiment II: swabs socked in natural estrual discharge or Eau D'Estrus were presented to male dogs and behavioral arousal (Exp. II a) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Alimentary lymphoma can appear with different features in the GI tract: It can occur as a focal or multifocal hypoechoic intestinal mass with transmural loss of wall layering, causing partial stenosis of the intestinal lumen or it may appear as a normal or increased intestinal wall thickness with preservation of intestinal layers (Penninck, 1998;Lingard et al, 2009;Gieger, 2011;Gaschen, 2011). Furthermore, it is the most common neoplastic cause of diffuse infiltration and wall thickening in cats that can appear similar to Inflammatory Bowel Disease (IBD) (Gaschen, 2011;Gianella et al, 2017). In cats, AL, as previously told, is the most commonly encountered form of lymphoma and the three main histological types, LGAL, HGAL and LGLL, have different diffusion, aggressiveness and prognosis.…”
Section: Intestinementioning
confidence: 99%
See 1 more Smart Citation
“…Alimentary lymphoma can appear with different features in the GI tract: It can occur as a focal or multifocal hypoechoic intestinal mass with transmural loss of wall layering, causing partial stenosis of the intestinal lumen or it may appear as a normal or increased intestinal wall thickness with preservation of intestinal layers (Penninck, 1998;Lingard et al, 2009;Gieger, 2011;Gaschen, 2011). Furthermore, it is the most common neoplastic cause of diffuse infiltration and wall thickening in cats that can appear similar to Inflammatory Bowel Disease (IBD) (Gaschen, 2011;Gianella et al, 2017). In cats, AL, as previously told, is the most commonly encountered form of lymphoma and the three main histological types, LGAL, HGAL and LGLL, have different diffusion, aggressiveness and prognosis.…”
Section: Intestinementioning
confidence: 99%
“…Clinical signs depend on which portion of the GI tract is involved and usually include chronic vomiting and/or diarrhea, gastro-intestinal blood loss (hematemesis, melena and/or hematochezia) with weight loss that could result from anorexia, malabsorption and/or maldigestion, loss of protein or generalized tumour cachexia. Laboratory abnormalities may include panhypoproteinemia, microcytic hypochromic anemia related to chronic gastro-intestinal blood loss and malabsorption (Willard, 2012;Terragni et al, 2014b;Gianella et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, the clinical signs of LGAL are not pathognomonic making diagnosis challenging. During diagnostic investigations, metabolic diseases, endocrinopathies, infectious diseases, chronic cholangitis, pancreatitis, and exocrine pancreatic insufficiency should first be ruled out using clinicopathological testing and diagnostic imaging [ 79 , 82 ]. Thereafter, LGAL should be differentiated from other gastrointestinal tract diseases such as food-responsive enteropathy (FRE) and IBD.…”
Section: Diagnosismentioning
confidence: 99%
“…To the authors’ knowledge, no study has yet demonstrated the ability of paraclinical data to differentiate LGAL from IBD. However, failure to recognise and correct hypocobalaminaemia is known to delay clinical recovery, even when specific therapy for AL or IBD is instituted [ 82 , 86 ]. Hypoalbuminaemia is reported in 70% of cats with AL, 49% with LGAL, and 77% with IBD respectively [ 20 , 87 ].…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation